BMP15 regulates the inhibin/activin system independently of ovulation rate control in sheep. Issue 4 (April 2017) - Estienne, Anthony; Lahoz, Belén; Jarrier, Peggy; Bodin, Loys; Folch, José; Alabart, José-Luis; Fabre, Stéphane; Monniaux, Danielle
Abstract : Polymorphisms in the gene encoding bone morphogenetic protein 15 (BMP15) have been associated with multiple ovulations in sheep. As BMP15 regulates inhibin expression in rodents, we assumed that the ovarian inhibin/activin system could mediate part of the effect of BMP15 mutations in the regulation of ovulation rate in sheep. To answer this question, we have studied the effects of two natural loss-of-function mutations of BMP15 on the expression of components of this system. The FecX R and the FecX Gr mutations, when present respectively in Rasa Aragonesa ewes at the heterozygous state and in Grivette ewes at the homozygous state, were associated with a twofold increase in ovulation rate. There were only small differences between mutant and wild-type ewes for mRNA expression of INHA, INHBA, ACVR1B, ACVR2A, FST or TGFBR3 in granulosa cells and inhibin A or activin A concentrations in follicular fluid. Moreover, the effects of mutations differed between breeds. In cultures of granulosa cells from wild-type ewes, BMP15, acting alone or in synergy with GDF9, stimulated INHA, INHBA and FST expression, but inhibited the expression of TGFBR3 . Activin A did not affect INHBA expression, but inhibited the expression of ACVR2A also. The complexity of the inhibin/activin system, including positive and antagonistic elements, and the differential regulation of these elements by BMP15 and activin can explain that the effects of BMP15 mutations differ when present in different genetic backgrounds. In conclusion, the ovarian inhibin/activin system is unlikely to participate in the increase of ovulation rate associated with BMP15 mutations in sheep.